СОВРЕМЕННЫЕ СКОРОСТИ РАЗРУШЕНИЯ БЕРЕГОВ РОССИЙСКОГО ПОБЕРЕЖЬЯ АЗОВСКОГО МОРЯ - Ивлиева О.В.; Бердников С.В. (My University, 2005)
Average rate of abrasion material supplied over the last 20 years in north part of Taganrog bay reaches 7600 m'/year per 1 km of the bank, and loss of land is 0.6 m/year. The southern beach of bay retreats by 1.5-1.7 m/year, the volume of sediments supplied reaches 13000 m3/year. These values correspond to years characterized by strong heave.
Keywords: 551.435.3(262.54)